STRATEGI GURU DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MEMBENTUK AKHLAK SISWA DALAM PEMBELAJARAN DARING DI SMP NEGERI 9 MALANG - Zahrotul Jannah; Maskuri Maskuri; Mutiara Sari Dewi (VICRATINA, 2021)
This study aims to describe the teacher's strategy in establish students' morals. because establish students' morals are the most important mission that must be carried out by Islamic religious education teachers and of course they have their strategies or ways in carrying out the process, especially in online learning today. The strategy of Islamic religious education teachers in establishing students' morals will also greatly affect the level of understanding and practice of moral values themselves, especially in practicing noble values, both in institutions and non-institutions.